Kontribusi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) bagi Peningkatan Pendapatan Asli Daerah di Kabupaten Sidoarjo - Surendro Nurbawono (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study first, to determine and analyze the problems in delegating authority management of land and building tax of rural and urban from central government to the Sidoarjo Regency governments. Second, determine and analyze the contribution of land and building tax of rural and urban for improvement local revenue in the Sidoarjo Regency. The research method used qualitative approach. The results showed first, the problem condition concluded inconsistencies related regulations in delegating credit to the Sidoarjo Regency government. Second, the contribution of its authority delegation increased revenue until 100%, balancing the interests of budgetary for discretionary policies in the regency/city, explored potential revenue for a wider network of bureaucracy, improved the quality of services to taxpayers, as well as improved accountability for the use of land and building tax of rural and urban.